2014
DOI: 10.3389/fnana.2014.00100
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of calretinin-containing hippocampal interneurons to temporal lobe epilepsy

Abstract: This review focuses on the vulnerability of a special interneuron type—the calretinin (CR)-containing interneurons—in temporal lobe epilepsy (TLE). CR is a calcium-binding protein expressed mainly by GABAergic interneurons in the hippocampus. Despite their morphological heterogeneity, CR-containing interneurons form a distinct subpopulation of inhibitory cells, innervating other interneurons in rodents and to some extent principal cells in the human. Their dendrites are strongly connected by zona adherentiae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 132 publications
(281 reference statements)
2
19
0
Order By: Relevance
“…CaR that specifically marks selective neuron populations in various areas of the central nervous sytem (Eyles et al, 2002; Ulfig, 2002; Grateron et al, 2003; Džaja et al, 2014; Hladnik et al, 2014; Tóth and Maglóczky, 2014) including the vertebrate retina (Völgyi et al, 1997; Gábriel and Witkovsky, 1998; Gábriel et al, 1999; Araki and Hamassaki-Britto, 2000). CaR has also been shown to be expressed by AII cells in a number of examined mammalian species.…”
Section: Resultsmentioning
confidence: 99%
“…CaR that specifically marks selective neuron populations in various areas of the central nervous sytem (Eyles et al, 2002; Ulfig, 2002; Grateron et al, 2003; Džaja et al, 2014; Hladnik et al, 2014; Tóth and Maglóczky, 2014) including the vertebrate retina (Völgyi et al, 1997; Gábriel and Witkovsky, 1998; Gábriel et al, 1999; Araki and Hamassaki-Britto, 2000). CaR has also been shown to be expressed by AII cells in a number of examined mammalian species.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest, the selective vulnerability of multiple subsets of CR+ cells in the hippocampus may occur in a temporal-lobe epilepsy model, a good predictor of neuronal vulnerability to excitotoxicity. Those cells that remain exhibit pathologic dendritic varicosities and a loss of dendritic complexity and synapses, as a result of excitotoxic injury (Tóth et al 2010; Tóth and Maglóczky 2014). Patients with epilepsy can have fewer nNOS+ interneurons within CA1 (Leite et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal interneurons interact as part of a functional network and it is clear that the removal of even one cell type from the network can have drastic effects on information processing, pyramidal cell excitation, and consequent behavioral outcomes (Moga et al 2002; Dugladze et al 2007; Goldin et al 2007; Tóth et al 2010; Peng et al 2013; Long et al 2014; Lovett-Barron et al 2014; Lovett-Barron and Losonczy 2014; Tóth and Maglóczky 2014; Orbán-Kris et al 2015). Importantly, the susceptible nNOS+/NPY− interneurons of the stratum pyramidale and the stratum radiatum, PV+ cells of the stratum pyramidale, and SST+ interneurons of the stratum oriens form a microcircuit known to be involved in a complex feedback loop/input gating mechanism that regulates network synchronization within CA1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LTP of the perforant path–granule cell synapse was reduced in mice lacking calretinin compared with wild-type mice 69 . Although intriguing, the study was limited by the constitutive nature of the knockout and the expression of calretinin in cells other than mossy cells (including a subtype of interneuron in the dentate gyrus 70 ). However, other methods have also shown that mossy cells may facilitate or even be required for LTP of the perforant path input to granule cells.…”
Section: Mossy Cell Function In the Dentate Gyrusmentioning
confidence: 99%
“…It has also been proposed that mossy cell-mediated excitation of granule cells is increased after insults that lead to TLE, causing hyperexcitability 1,104106,111,112 . However, hyperexcitability could also be caused by a loss of HIPP cells 97 or calretinin-expressing interneurons 70 . Diverse changes in other aspects of the inhibitory control of granule cells 113 , including changes in the subunit composition of type A GABA receptors 114116 , have led to the current consensus that a loss of mossy cells may contribute to TLE but is unlikely to be fully responsible for it.…”
Section: Mossy Cell Vulnerabilitymentioning
confidence: 99%